Equality for Women : Where Do We Stand on Millennium Development Goal 3? - Buviníc, Mayra; Morrison, Andrew R.; Ofosu-Amaah, A. Waafas; Sjöblom, Mirja (Washington, DC : World Bank, 2012)
There is compelling evidence of the importance of gender equality for poverty reduction and sustainable growth. So it should come as no surprise that most development actors-international agencies, bilateral donors, and most developing countries, have an official policy for promoting gender equality. Millennium Development Goal 3 (MDG3) on gender equality and women's empowerment is shared global commitment. With only seven years remaining until the end date for the MDGs, it is an opportune time to take stock of where the world stands in terms of progress toward gender equality. This volume documents trends both on the official MDG3 indicators and on an expanded set of indicators that provide a more complete measure of gender equality, especially in the area of women's economic empowerment. The message that emerges is both hopeful and sobering: progress toward equality in capabilities has been considerable, but progress toward equality of opportunities for women's economic livelihoods leaves much to be desired. Beyond tracking trends toward gender equality, the volume reviews different measures of gender equality and estimates the financial resources required to achieve this objective. While necessarily imprecise, such estimates can provide a rough guide as to whether the level of effort devoted by international donors and developing countries is adequate in the area of women's economic empowerment.